VIRTUAL WLAN: EXTENSION OF WIRELESS NETWORKING INTO VIRTUALIZED ENVIRONMENTS - Aljabari, Ghannam; Eren, Evren (International Journal of Computing, 2011)
In wired Ethernet networks (IEEE 802.3), a physical network interface can be connected to different network segments or shared among multiple virtual machines. In wireless LAN (IEEE 802.11) sharing a wireless network interface is recognized to be a difficult task. However, virtualization can solve this problem. In this paper we will introduce a software platform for hosting multiple virtual wireless networks over a shared physical infrastructure by means of open source virtualization techniques. We present the design, implementation, and performance testing of this platform. Results have shown that the hosting platform can extend wireless networking into virtualized environments without compromising the performance, isolation, or wireless LAN security mechanisms.